IDENTIFIKASI GOLONGAN SENYAWA ANTIOKSIDAN DENGAN MENGGUNAKAN METODE PEREDAMAN RADIKAL DPPH EKSTRAK ETANOL DAUN Cordia myxa L. - Rezki Amriati Syarif; Muhajir Muhajir; Aktsar Roskiana Ahmad; Abd. Malik (Jurnal Fitofarmaka Indonesia, 2015)
Cordia myxa L .leaf is a plant from Boraginaceae family which is traditionally used as medicine of several skin diseases . The purpose of thid research is to know the chemical compound antioxidant activity of ethanolic extract of Cordia myxa L. leaf. The used extraction method was maceration method using 70% as solvent. Identification of coumpound group used  color reaction and  precipitation method respectively. While antioxidant activity test used free radical scavenging method of DPPH (1,1-dyphenyl-2 pycril Hydrazil). From the extraction result, that was found that %redamen of ethanolic extract of  Cordia myxa L .leaf 2.76%. While the determination of chemical compound showed that ethanolic extcract of  Cordia myxa L .leaf containing steroid, flavonoid, saponin, and phenol. The result antioxidant activity assay showed that ethanolic extract of Cordia myxa L .leaf has intermediate free antiradical activity with IC50 value 54.92 µg/mL. But it is potensial is lower than Quarcetin which has IC50 value 0.52 µg/mL.